Inventarisasi Selaginellaceae di Kawasan Taman Wisata Alam Sicike–Cike Kabupaten Dairi Sumatera Utara - Afrizal Azali; Emmy Harso Kardhinata; Jamilah Nasution (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2020)
Natural Park (TWA) Sicike-Cike is highland tropical  rain forest  located in  Kabupaten  Dairi,  North Sumatera. The park is home of various ferns. The purpose of this research is to inventory fern’s species classified as Selaginellaceae, in the above Park. Samples were obtained using “purposive sampling’(descriptive method) by exploration technique, there were 5 Specias identified; Selaginella intermedia, Selaginella longiaristata, Selaginella ornata, Selaginella plana, and Selaginella willdenowii.